2015
DOI: 10.1123/japa.2014-0115
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Levels of Physical Activity in Older Patients During Hospitalization at an Acute Geriatric Ward: A Prospective Cohort Study

Abstract: Lack of activity during hospitalization may contribute to functional decline. The purpose of this study was to investigate (1) the time spent walking during hospitalization by geriatric patients referred to physical and/or occupational therapy and (2) the development in time spent walking during hospitalization. In this observational study, 24-hr accelerometer data (ActivPal) were collected from inclusion to discharge in 124 patients at an acute geriatric ward. The median time spent walking was 7 min per day. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
80
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 0 publications
14
80
0
1
Order By: Relevance
“…Comparability of walking times achieved in our study with those in previous studies monitoring activity in geriatric rehabilitation using wearable devices [2833] are problematic because of differences in population characteristics (including primary diagnosis and acuity), setting (acute, sub-acute or post-acute rehabilitation), period of monitoring and activity measured (eg step count, walking, or ‘uptime’ which includes standing and walking). For example, compared with a baseline median daily walking time of 10 minutes in the current study, daily walking activity varied from 4 minutes in a study of a comparable population referred for rehabilitation therapy [33], to 7 minutes in a study of patients rehabilitated following hip fracture [28] and 23 minutes in moderately impaired elderly stroke patients [31].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Comparability of walking times achieved in our study with those in previous studies monitoring activity in geriatric rehabilitation using wearable devices [2833] are problematic because of differences in population characteristics (including primary diagnosis and acuity), setting (acute, sub-acute or post-acute rehabilitation), period of monitoring and activity measured (eg step count, walking, or ‘uptime’ which includes standing and walking). For example, compared with a baseline median daily walking time of 10 minutes in the current study, daily walking activity varied from 4 minutes in a study of a comparable population referred for rehabilitation therapy [33], to 7 minutes in a study of patients rehabilitated following hip fracture [28] and 23 minutes in moderately impaired elderly stroke patients [31].…”
Section: Discussionmentioning
confidence: 66%
“…For example, compared with a baseline median daily walking time of 10 minutes in the current study, daily walking activity varied from 4 minutes in a study of a comparable population referred for rehabilitation therapy [33], to 7 minutes in a study of patients rehabilitated following hip fracture [28] and 23 minutes in moderately impaired elderly stroke patients [31]. Increase in walking time over the duration of rehabilitation shows similar wide variation, depending on diagnostic group and period of monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that patients remained largely inactive (sitting and lying = 89.2 %) during hospitalization. The physical inactivity observed in hospitalized patients has previously been described in the elderly [42] and patients with chronic lung disease [18,19]. Villumsen et al [42] demonstrated that elderly patients nearing hospital discharge spent approximately 10 min/day walking.…”
Section: Discussionmentioning
confidence: 99%
“…The physical inactivity observed in hospitalized patients has previously been described in the elderly [42] and patients with chronic lung disease [18,19]. Villumsen et al [42] demonstrated that elderly patients nearing hospital discharge spent approximately 10 min/day walking. In COPD patients, the average daily walking time during hospitalization was less than 10 min/day [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…3,13,16,26,27 In hospitals, the ambulation and training of medical patients, however, seem to have an even lower priority in practice than patient nutrition intake. 7,28,29 Many barriers seem to be present regarding training and ambulation, as well as to providing nutrition for patients, even though nurses are present, and may be the relevant partner, closest to the patient. 28,30,31 The aim of our study was to assess whether it was possible to improve muscle function in acutely ill patients by an active approach based on evidence-based nutritional support and early physiotherapy, in an intervention closely integrated in the daily activities of the ward.…”
Section: Introductionmentioning
confidence: 96%